PENGARUH DIGITALISASI KEUANGAN DAN LITERASI KEUANGAN TERHADAP INKLUSI KEUANGAN BERKELANJUTAN GENERASI Z DI ERA EKONOMI DIGITAL - M. Rizky Wijaya; Purwita Sari; Ratih Anggraini Siregar; Tika Nirmala Sari; Ahmad Rivaldo Tarigan (Journal Economic Management and Business, 2026)
The rapid advancement of digital technology has significantly transformed financial services and consumer financial behavior, particularly among Generation Z as digital natives. This study aims to examine the influence of financial digitalization and financial literacy on sustainable financial inclusion among Generation Z in the digital economy era. A quantitative approach was employed using a survey method with structured questionnaires. The study involved 145 Generation Z respondents aged 17–27 years in Indonesia who actively use digital financial services, selected through purposive sampling. Data were analyzed using multiple linear regression. The results indicate that financial digitalization and financial literacy have a positive and significant effect on sustainable financial inclusion, both partially and simultaneously. These findings highlight that the success of sustainable financial inclusion depends not only on technological accessibility but also on individuals’ financial knowledge and responsible financial behavior.